2017
DOI: 10.1167/iovs.17-22736
|View full text |Cite
|
Sign up to set email alerts
|

Corneal and Retinal Neuronal Degeneration in Early Stages of Diabetic Retinopathy

Abstract: PURPOSE. To examine the neuronal structural integrity of cornea and retina as markers for neuronal degeneration in nonproliferative diabetic retinopathy (NPDR).METHODS. Participants were recruited from the broader Brisbane community, Queensland, Australia. Two hundred forty-one participants (187 with diabetes and 54 nondiabetic controls) were examined. Diabetic retinopathy (DR) was graded according to the Early Treatment Diabetic Retinopathy Study (ETDRS) scale. Corneal nerve fiber length (CNFL), corneal nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 62 publications
1
31
1
1
Order By: Relevance
“…14 This is the first longitudinal study in young adolescents with T1DM and it shows no significant change in epithelial, stromal, and endothelial cell densities over 2 years. With regard to early nerve fiber alterations, previous studies have shown a reduction in corneal and retinal nerve fiber parameters prior to the development of retinopathy 13,27 and a relatively greater reduction in CNFL in patients with T1DM compared to T2DM. 28 In the present study over 2 years, there was a significant decrease in the distal branches (CNBD and CNTBD) in young patients with T1DM without DR and a reduction in more proximal nerves (CNFD) in patients with DR.…”
Section: Discussionmentioning
confidence: 99%
“…14 This is the first longitudinal study in young adolescents with T1DM and it shows no significant change in epithelial, stromal, and endothelial cell densities over 2 years. With regard to early nerve fiber alterations, previous studies have shown a reduction in corneal and retinal nerve fiber parameters prior to the development of retinopathy 13,27 and a relatively greater reduction in CNFL in patients with T1DM compared to T2DM. 28 In the present study over 2 years, there was a significant decrease in the distal branches (CNBD and CNTBD) in young patients with T1DM without DR and a reduction in more proximal nerves (CNFD) in patients with DR.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that larger ganglion cells in the retina might have been further damaged than the small ganglion cell, the presence of two parallel magnocellular and parvocellular pathways of processing for depth perception is supported. The extensive evidence regarding the thickness reduction in the ganglion cell layer and the retinal nerve fiber layer in the early stages of DR [2][3][4][5][6][8][9][10]29,[31][32][33] further supports the parallel pathways of depth perception. Our findings also do not rule out the serial model of processing.…”
Section: Discussionmentioning
confidence: 92%
“…Recent OCT findings revealed that pockets of ganglion cell volume loss have been observed in patients with very mild NPDR compared with the non-diabetic group. 29 However the type of the cell in these pockets were not clear. There is also evidence that retrograde axonal transport is impaired for large and medium retinal ganglion cell types in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of neuronal damage in early stages of diabetes has been demonstrated in laboratory studies, 4 – 7 and the findings have been described clinically in a study by Srinivasan et al, who examined the neuronal structural integrity of the cornea and retina as markers for neuronal degeneration in non-proliferative diabetic retinopathy. 36 They assessed the corneal nerve fiber length (CNFL), corneal nerve branch density (CNBD), and the corneal nerve fiber tortuosity (CNFT), and reported that shorter CNFLs were significantly associated with the severity of the nonproliferative diabetic retinopathy, CNBD, and CNFT. According to Srinivasan et al, CNFL may be a better marker, than CNBD and CNFT, for detecting corneal neuronal degeneration in patients with mild nonproliferative diabetic retinopathy, compared with controls and those with diabetes but without retinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…According to Srinivasan et al, CNFL may be a better marker, than CNBD and CNFT, for detecting corneal neuronal degeneration in patients with mild nonproliferative diabetic retinopathy, compared with controls and those with diabetes but without retinopathy. 36 …”
Section: Introductionmentioning
confidence: 99%